Safety, Pharmacokinetics and Preliminary Efficacy of IL4-Rα Monoclonal Antibody AK120 in Both Healthy and Atopic Dermatitis Subjects: A Phase I, Randomized, Two-Part, Double-Blind, Placebo-Controlled, Dose-Escalation, First-In-Human Clinical Study - Christopher John Wynne; Alexandra Cole; Charlotte Lemech; Guoqin Wang; Yu Zhang; Benchao Chen; Max Wang; Baiyong Li; Michelle Xia; Rodney Sinclair (Adis, Springer Healthcare, 2023)
Abstract Introduction Interleukin-4 (IL-4) and interleukin-13 (IL-13) are two essential cytokines involved in the T helper 2 (Th2)-mediated inflammatory response to diseases, such as atopic dermatitis (AD). AK120 is a humanized immunoglobulin G subclass 4 (IgG4) monoclonal antibody (mAb) directed against the IL-4 receptor alpha (IL-4Rα) subunit shared by the IL-4 and IL-13 receptor complexes. This mAb inhibits the signaling of the IL-4 and IL-13 cytokines. Methods The study consisted of two parts. Part 1 was a single ascending dose (SAD) study with five cohorts (receiving 15, 50, 150, 300 or 600 mg of AK120, respectively) of healthy subjects; part 2 was a multiple ascending dose (MAD) study with four cohorts (receiving AK120 at doses of 300 mg once every 2 weeks [Q2W], 300 mg once weekly [QW], 150 mg QW or 75 mg QW) of subjects with AD. A total of 81 subjects (40 in part 1, 41 in part 2) were enrolled in the study. Results The compound was safe and well tolerated in both a SAD up to 600 mg in healthy subjects and in a MAD from 75 to 600 mg in subjects with AD. The exposure of AK120 increased in an approximately dose-dependent manner upon subcutaneous dosing. The levels of the biomarkers serum thymus and activation-regulated chemokine ligand 17 (TARC/CCL17) and immunoglobulin E decreased from baseline after AK120 administration, indicating the inhibition of the IL-4/IL-13 signaling pathways. AK120 showed improved Eczema Area and Severity Index (EASI) scores, and the proportion of subjects with Investigator Global Assessment (IGA) score 0/1 increased after AK120 treatment. Conclusions AK120 exhibited an acceptable safety profile in healthy and AD subjects, and showed preliminary efficacy. These findings support the continued investigation of AK120 for treating AD. Clinical Trial Registration ClinicalTrials.gov identification number: NCT04256174.